Gonococcal Surveillance Australia: Quarter 3, 2012 - Lahra, Monica M; Australian Gonococcal Surveillance Programme (Communicable Diseases Intelligence, 2013)
The Australian National Neisseria Network (NNN) comprises reference laboratories in each state and territory that report data on sensitivity to an agreed group of antimicrobial agents for the Australian Gonococcal Surveillance Programme (AGSP). The AGSP data are presented quarterly in tabulated form, as well as in the AGSP annual report. This report presents national gonococcal antimicrobial resistance surveillance data for the indicated quarter.